The Standardisation of handoffs in a large academic paediatric emergency department using I-PASS - Binita Patel; Cara Doughty; Melissa Sydow Chladek; Kyetta Alade; Marideth Rus; Joan Shook; Kim LIttle-Weinert (BMJ Open Quality)
Background and objectives Despite the American College of Emergency Physicians and American Academy of Pediatrics recommendations for standardised handoffs in the emergency department (ED), few EDs have an established tool. Our aim was to improve the quality of handoffs in the ED by establishing compliance with the I-PASS handoff tool.Methods This is a quality improvement (QI) initiative to standardise handoffs in a large academic paediatric ED. Following review of the literature and focus groups with key stakeholders, I-PASS was selected and modified to fit departmental needs. Implementation throughPlan–Do–Study–Act cycles included the development of educational materials, reminders and real-time feedback. Required use of I-PASS during designated team sign-out began in June 2016. Compliance with the handoff tool and handoff deficiencies was measured through observations by faculty trained in I-PASS. As a balancing measure, time to complete handoff was monitored and compared with preintervention data.Results Compliance with I-PASS reached 80% within 6 months, 100% within 7 months and sustained at 100% during the remainder of the study period. The average percent of omissions of crucial information per handoff declined to 8.3%, which was a 53% decrease. Average percentage of tangential information and miscommunications per handoff did not show a decline. The average handoff took 20 min, which did not differ from the preintervention time. Survey results demonstrated a perceived improvement in patient safety through closed-loop communication, clear action lists and contingency planning and proper patient acuity identification.Conclusions I-PASS is applicable in the ED and can be successfully implemented through QI methodology contributing to an overall culture of safety.